Elaboração e evidências de validade de um instrumento para avaliação do uso de estratégias metacognitivas por graduandos e pós-graduandos - Duarte, Laura Andrelynne Durans (Universidade Federal de São Carlos, 2026)
Metacognition refers to an individual's thoughts and knowledge about their own cognitive processes, and the subsequent ability to consciously adjust them to enhance their learning and problem-solving processes. Metacognitive strategies are components of metacognition, defined as practices adopted to monitor progress in performing a task. To assess these strategies, Psychology lacks adequate psychometric instruments with good psychometric properties. This dissertation is organized into two studies that sought to develop a new psychometric instrument to assess the use of metacognitive strategies in the university population and verify its psychometric properties. Study 1 focused on the initial development of the items and obtaining evidence of content validity through expert analysis and semantic analysis. After evaluation by judges and the target audience (undergraduate and graduate students), the Metacognitive Strategies Scale (MSS) was finalized with 48 statements. The results indicated that the MSS reached good content validity indicators, with Aiken V indices between 0.75 and 1.00, and an average semantic validity of 8.99, which attests to the clarity of the writing for the target audience. Study 2 continued the objectives, investigating the validity by internal structure, by relationship with external variables, and the reliability of the MSS in 149 undergraduate and graduate students. Exploratory Factor Analysis (EFA) and Exploratory Graphical Analysis (EGA) indicated a theoretically coherent two-dimensional solution of 17 items, composed of the factors Planning (P) and Monitoring and Regulation (MR). The evidence of convergent validity was supported by positive, moderate, and statistically significant correlations between the total MSS scores and the Metacognitive Awareness Inventory (MAI) (ρ = 0.48) and Learning and Studying Strategies Inventory (LASSI) (ρ = 0.56) instruments. Additionally, the MSS demonstrated optimal precision, with internal consistency coefficients (McDonald's ω and Cronbach's α) ranging from 0.78 to 0.85. In summary, the evidence collected suggests that the Metacognitive Strategies Scale constitutes a good quality psychometric instrument, suitable for measuring these strategies in the university target audience.
Development and validity evidence of an instrument for assessing the use of metacognitive strategies by undergraduate and graduate students.
Keywords: metacognição; estratégias metacognitivas; construção de instrumento; CIENCIAS HUMANAS::PSICOLOGIA::FUNDAMENTOS E MEDIDAS DA PSICOLOGIA; 4. Educação de Qualidade